If i ran the circus - Dr. Seuss (London : HarperCollins Children's Books, 2017)
In this delightful classic from the one and only Dr. Seuss, Morris McGurk dreams about staging the world's greatest show! Join Morris McGurk for the world's greatest show, packed with the most tremendous, stupendous acts ever seen, from the Spotted Atrocious -- a beast most ferocious -- to the Drum-Tummied Snumm from the country of Frumm. If only he ran the circus..
Keywords: |a Circus -- Poetry; Stories in rhyme; Fantasy